(untitled) (International Journal of Environmental Sciences, 2025)
The research paper titled “The Rendition of Jack Solomon’s ‘What’s in a Name? The Ideology of Cultural Classification’ in the Aura of Postmodernism” is based on the operational logic of demarcating domains or areas in relation to conceptualization. The study related to classification and categorization of different ideas, concepts and disciplines subverts the very basis of classification and categorization of these entities that is perceived as compartmentalization of ideas or concepts or else disciplines into rigid compartments without acknowledging the existence of the fuzzy areas or the overlapping domains in between these compartments. The study utilizes the critical theory of Postmodernism to investigate the taxonomic relationships based on “Benjamin Bloom’s Taxonomy” between different categories thereby questioning the rationality behind classification, categorization, and the creation of superordinate and hyponyms in relation to ideas, concepts, and disciplines. The traditional labels and categories loose relevance. In Postmodernism, a confusion or a lack of choice or a lack of structure or else a fragmentation of a structure brings into play the possibility of incessant choice thereby upholding infinite possibilities of permutations and combinations in relation to the formation of categories or of introducing overlaps among two or more categories. There is a transformation of the self with the introduction of “pick ‘n’ mix. It provides the opportunity to an entity to create its own identity and to bring greater pluralism in modern life. There are no absolutes. The predictability in relation to the systems is reduced. There is fluidity in the systems of signification, the boundaries of the systems are porous. Globalization has narrowed space and time, there has been a widespread technological intervention in the lives of the homo sapiens thereby making access to information easier and intensifying the search for truth which has increased the possibilities of permutations and combinations.